Standardization of artificial screening technique for okra enation leaf curl disease resistance in wild okra (Abelmoschus moschatus ssp. Moschatus) germplasm - KUMARI, POOJA; SINGH, S P; GANGOPADHYAY, K K; CHALAM, V CELIA; PANDEY, CHITHRA DEVI; YADAV, SATISH KUMAR (The Indian Journal of Agricultural Sciences, 2022)
Okra enation leaf curl disease (OELCuD) is a recently emerged whitefly insect vector transmissible viral disease of okra which adversely affects the quality and quantity of okra fruits. Okra enation leaf curl virus (OELCuV) is a main disease causative agent. Two year (kharif 2018 and 2019) field experiments were conducted at research farm of ICAR-National Bureau of Plant Genetic Resources, Pusa, New Delhi for field screening of 10 wild okra (Abelmoschus moschatus ssp. moschatus) accessions, viz. EC360586, EC360794, EC360830, EC360900, EC359730, EC359836, EC359870, EC360351, EC361111 and EC361171. Out of 10 accessions, 4 accessions, viz. EC360794, EC360586, EC360830 and EC361171 showed resistance (R) reaction in both the seasons. Whitefly population was also monitored in both the rainy (kharif) season, since, OELCuD is transmitted by whitefly insect vector. Majority (>77%) of okra genotypes were moderately preferred by the whiteflies. To further validate the resistance reaction in these 4 field resistant accessions, artificial screening experiment was conducted using viruliferous whitefly vector and VRO 6 as susceptible check. Prominent okra enation leaf curl symptom appeared after a minimum incubation period of 15 days under controlled conditions. Betasatellite (DNA-β) molecule of OELCuV was amplified (1.3 kb) using PCR for virus detection and these 4 accessions were found free from virus. These 4 promising accessions would serve as resistance source in breeding programmes to develop varieties resistant to OELCuV.